increasing direct delivery through adding hub in proposed cities for e-commerce industry (case study : Lazada Indonesia) - Wibowo, Muhammad Nurhadi; Wiyana, Aldo F (The Indonesian Journal of Business Administration, 2015)
Abstract.Internet growth recently has created a new era that called virtual world that many people can connect with other people without limitation. Internet user in Indonesia has reach almost 15% of total population and become the largest Internet user in Southeast Asia. This phenomena has supported retail online industry that we known as e-commerce.To identify the company’s problem, there are several interviews with distribution manager of Lazada Indonesia. Currently, to perform product shipment to customers Lazada Indonesia use internal logistic service provider (Lazada express) and external logistic service provider (JNE, RPX, PANDU). The problems faced by Lazada Indonesia are to determine cities for adding hub to increasing direct delivery of Lazada Indonesia through Lazada express. Lazada Indonesia wants to increase their direct delivery to increase profit and to reduce lead-time. By using internal logistic service provider through Lazada express Lazada Indonesia can increase their economic of scale compare to using external service provider. Another reason is to reduce lead-time, because by using internal logistic service provider customer can receive order less than 2 days. In this study, there are three analyses to proposed cities to solve the current problem. First analysis is to decrease chosen amount of cities from 34 to 10 cities using 1% indicator based on interview with distribution manager of Lazada Indonesia. Second analysis is to determine scale of priority for each cities using weighted decision matrix. Third analysis is to forecast demand for Lazada Indonesia to determine cost to create new hub in proposed cities. The requirement of this analysis is to be a solution for Lazada express to increase their direct delivery by adding new hub. After performed three analysis based on mentioned analysis, there are 10 cities proposed to create new hub. The cities are Semarang, Yogyakarta, Palembang, Surabaya, Banjarmasin, Denpasar, Pekanbaru, Padang, Medan, and Makassar.Keywords: Lazada Indonesia, e-commerce, third party logistic, network and supply chain design.